Effect of Organisational Commitment in Psychological Contract Breach-Organisational Citizenship Behaviour Bond among Medical Doctors: During a breach, does organisational commitment reduce medical doctors' tendency to be bad organisational citizens? - Koomson, Samuel (International Journal of Scientific Research and Management (IJSRM), 2020)
Medical doctors are responsible for leading the care of patients. They are perhaps the most valuable assets of healthcare organisations. Yet, indications signal that medical doctors operating in the Upper East and West Regions of Ghana are bedevilled with severe breaches in their psychological contract, which could probably result in low commitment to their organisation and subsequently, stifle their tendency to be good organisational citizens. The study therefore investigated the interceding effect of organisational commitment in the nexus between psychological contract breach and organisational citizenship behaviour among medical doctors in the Upper East and Upper West Regions of Ghana. 214 medical doctors participated in the study. A validated, semi-structured and self-administered questionnaire was employed. The data collected was subjected to Kaiser-Meyer-Olkin measure of sampling adequacy and Bartlett test of sphericity, as well as reliability and validity tests. Mediating effect was conducted. Control variables were sex, age, employment type and tenure. Significant level was set at 5%. Partial-least squares structural equation modelling was used to analyse the data, with the help of Smart PLS 3.0M.3 software. Consistent with expectations, organisational commitment partially mediated the association between psychological contract breach and organisational citizenship behaviour among medical doctors working in these two regions. The study therefore settled that organisational commitment lessened the effect of a psychological contract breach on the medical doctors’ tendency to be bad organisational citizens. The study therefore recommends managers of Ghana Health Service to consider improving the level of organisational commitment among the medical doctors.